Pengaruh Work-Life Balance Terhadap Kinerja Pegawai Lembaga Pemasyarakatan Kelas IIB Brebes - Ading Rifaldi; Padmono Wibowo (JOURNAL SAINS STUDENT RESEARCH, 2023)
In the modern era, work pressure and work demands are getting higher, making it difficult for many employees to balance their work life and personal life (work-life balance). This study aims to determine the effect of work-life balance on job performance in Class IIB Brebes Penitentiary. This research is a type of quantitative research. In this study, the locus of Class IIB Brebes Correctional Institutions was taken. This research has a population of 59 employees and 30 employees of Class IIB Brebes Correctional Institution were taken as a sample. Data was collected using a questionnaire with a Likert scale of 1 to 4 and processed using IMB SPSS. The results obtained are r = 0.819 and r2 = 0.671 which means that the relationship between variables is a strong positive. It is also known that the significance level is 0.000 <0.05. So that the Work-life balance variable and the job performance variable have a significant relationship. This means that work-life balance has an influence on improving employee performance.